1977
DOI: 10.2307/3350888
|View full text |Cite
|
Sign up to set email alerts
|

Education for This Life or for the Life to Come: Observations on the Javanese Village Madrasah

Abstract: Many who wrote of Indonesian education in the first decade or so of independence described its present and adumbrated its future almost entirely in terms of the supervision of the Ministries of Basic Educa tion and Culture and of Higher Education.Muslim schools in general tended to be given a somewhat apologetic side-reference as manifesta tions of a tradition which had lost its power for all but a few be nighted conservatives. 129

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Fauzi and Nur'aeni also identified in their research about the strong relationship between education and religious teachings. Ma'zumi (2012) highlighted real madrasah diniyah contribution to the national character development; Orr et al (1977) concluded that madrasas in rural areas become a model of character education in the present and future; Likewise, Zarkasi and Kusaeri (2018) emphasized that strengthening character education process is carried out by madrasah diniyah. Number of authors also confirm the close association of religious education with character education.…”
Section: Introductionmentioning
confidence: 99%
“…Fauzi and Nur'aeni also identified in their research about the strong relationship between education and religious teachings. Ma'zumi (2012) highlighted real madrasah diniyah contribution to the national character development; Orr et al (1977) concluded that madrasas in rural areas become a model of character education in the present and future; Likewise, Zarkasi and Kusaeri (2018) emphasized that strengthening character education process is carried out by madrasah diniyah. Number of authors also confirm the close association of religious education with character education.…”
Section: Introductionmentioning
confidence: 99%